Model Pembelajaran Radec (Read-Answer-Discuss-Explain And Create): Pentingnya Membangun Keterampilan Berpikir Kritis Dalam Konteks Keindonesiaan (Indonesian Journal of Learning Education and Counseling, 2019)
The purpose of writing this article is to describe the RADEC learning model in building critical thinking skills. This study is in the background by the need for a learning model that fits the Indonesian context to build critical thinking skills that can be used at the elementary school level. This study uses the literature review. This study produces one solution to be able to build critical thinking skills is to use the RADEC learning model (read-answer-discuss-explain and create). The approach in learning that is done by the teacher plays a role in fostering critical thinking skills. The teacher needs to use a learning model that can stimulate students' critical thinking skills.